A new theory of depression based on the serotonin/kynurenine relationship and the hypothalamicpituitary- adrenal axis - Leslie Alejandra Ramírez; Elsy Arlene Pérez-Padilla; Francisco García-Oscos; Humberto Salgado; Marco Atzori; Juan Carlos Pineda (Biomédica: revista del Instituto Nacional de Salud, 2018)
The serotonergic and immunological hypothesis of depression proposes that certain types of excessive stress distort the relationship between the activities of the innate immune and central nervous systems, so that the stress caused by an infection, or excessive psychological stress, activate toll-like receptors such as the TLR-4, the transcription factor NF-kB, the inflammasome NLRP3, as well as the secretion of interleukin-1 beta (IL-1β), interleukin-6 (IL-6) and other factors of the innate immune response, causing first, the general symptoms of the disease which appear with any infection, but also those characteristic of depressive illness such as dysphoria and anhedonia. The evidence indicates that, if the stimulus persists or recurs within 24 hours, the indole-2, 3-dioxygenase enzyme (IDO) of the kynurenine metabolic pathway, which increases the synthesis of quinolinic acid, is activated with an associated reduction of serotonin synthesis. Quinolinic acid activates NMDA receptors in the central nervous system and stimulates the secretion of interleukins IL-6 and 1L-1β, among others, promoting hyper-activity of the HPA axis and reinforcing a bias of the tryptophan metabolism to produce quinolinic acid, and interleukins by the innate immune system, further reducing the synthesis of serotonin and consolidating the depressive process. We discuss the evidence showing that this process can be initiated by either interleukin stimulated by an infection or some vaccines or excessive psychological stress that activates the HPA axis together with said innate immune response, causing a process of aseptic inflammation in the central nervous system.